Modified Chimeric Radial Collateral Artery Perforator Flap for Repairing Hand Composite Defects - Liu, Jun; Song, Dajiang; Wu, Song; Li, Jinsong; Deng, Xiangwu; Li, Kuangwen; Lv, Hongbin; Xu, Jian (Journal of Reconstructive Microsurgery, 2015)
Background The authors presented their clinical experience and demonstrated surgical methods for reconstructing complex bone and soft tissue defects of the hand by using modified chimeric radial collateral artery perforator flaps.Methods Surgical procedures that employed 16 modified chimeric radial collateral artery perforator flaps and 3 dual paddle flaps were performed in 16 patients. Among the patients, eight had defects in the metacarpal bones and eight had defects in the phalanx bones. The flaps were created with a skin paddle and humeral bone segments by using independent perforators. The flaps ranged in size from 5.5 × 2.0 to 7.5 × 4.5 cm, whereas the humeral fragments ranged in size from 1.5 × 0.5 to 4.0 × 1.5 cm. The pedicle of the flaps was divided and ligated below the level at which the radial collateral artery separates into anterior and posterior branches. The recipient vessels were the proper digital artery, the palmar subcutaneous vein (n = 12), the deep branch of the palmar ulnar artery (n = 4), and the venae comitantes. The cosmetic appearance of both donor and recipient sites was evaluated during a follow-up visit.Results Postoperative venous congestion occurred in two cases. The venous obstruction was reanastomosed after venous thrombectomy. The procedures were successful in both cases upon examination. All the flaps survived and all the donor sites were closed directly, leaving only a linear scar. Follow-up time ranged from 12 to 28 months. Bone components achieved union in all cases at an average of 5.4 months (ranging from 3 to 6 months). In two cases, the flap was defatted during the late postoperative period. Cosmetically acceptable results were achieved for the rest of the patients.Conclusion The modified chimeric radial collateral artery perforator flap is a good alternative for reconstructing complex bone and soft tissue defects of the hands.Level of Evidence This is a level IV, retrospective series.
Keywords: radial collateral artery; chimeric flap; composite defect; microsurgery